Seroprevalence of parvovirus B19 infection in patients with beta thalassemia major in Fayoum University Hospital - Mohamed E. Al Ghwass; Shahera M. El Shafei; Wael S. Mohamed; Basant S. Mohamed (Egyptian Pediatric Association Gazette, 2016)
Background and objectives: Patients with beta thalassemia major are at higher risk of acquiring reticulocytopenia, and cessation of erythropoiesis after exposure to parvovirus B19. The aim of the study was to detect the seroprevalence of parvovirus B19 infection in children with transfusion dependent beta-thalassemia major through the detection of its specific IgM and IgG in their sera by Enzyme-linked Immunosorbent Assay (ELISA) in the Pediatric Department of Fayoum University Hospital. Materials and methods: A cross sectional descriptive study was carried out from July to September 2013, in the Pediatric Department of Fayoum University Hospital in Egypt. A total of fifty-five children with beta-thalassemia major aged from 2 to 16 years were enrolled in the study. All patients were subjected to history taking, examination and investigations including; Complete blood count, serum creatinine, blood urea, hepatitis B surface antigen (HBsAg), anti hepatitis C virus antibody (anti HCV), reticulocytic count, anti B19 IgM and IgG. Results: Anti-B19 IgM antibodies (recent infection) were detected in 14.5% (8 patients), while anti B19 IgG antibodies (prior infection) were detected in 18.2% (10 patients) of transfusion dependent thalassemic patients. There was a significant statistical correlation between the history of other siblings with beta thalassemia major, the hepatitis C virus and hepatitis B virus infection regarding absent, prior and recent infection. Conclusion: Parvovirus B19 infection is detected in high rates among children with beta thalassemia major. Measures to avoid iatrogenic and nosocomial transmission have to be implemented including screening of donated blood for B19 especially blood given to patients with hematological disorders. Also data from this study support the need for introduction of an approved B19 vaccine that primarily protects children with thalassemia major against that infection.